2008
DOI: 10.1080/02701367.2008.10599458
|View full text |Cite
|
Sign up to set email alerts
|

The End-State Comfort Effect in Young Children

Abstract: The end-state comfort effect has been observed in recent studies of grip selection in adults. The present study investigated whether young children also exhibit sensitivity to end-state comfort. The task was to pick up an overturned cup from a table, turn the cup right side up, and pour water into it. Two age groups (N = 20 per group) were studied: preschool children (2-3 years old), and kindergarten students (5-6 years old). Each child performed three videotaped trials of the task. Only 11 of the 40 children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 21 publications
4
58
1
Order By: Relevance
“…In children, however, research on the development of the end-state comfort effect is limited, and the results are equivocal. In two studies, no developmental effect was found in children aged 2 to 6 years (Adalbjornsson, Fischman, & Rudisill, 2008;Manoel & Moreira, 2005). Adalbjornsson et al (2008) asked two groups of children (aged 2-3 and 5-6 years) to pick up a cup that was placed upside down.…”
Section: Introductionmentioning
confidence: 96%
“…In children, however, research on the development of the end-state comfort effect is limited, and the results are equivocal. In two studies, no developmental effect was found in children aged 2 to 6 years (Adalbjornsson, Fischman, & Rudisill, 2008;Manoel & Moreira, 2005). Adalbjornsson et al (2008) asked two groups of children (aged 2-3 and 5-6 years) to pick up a cup that was placed upside down.…”
Section: Introductionmentioning
confidence: 96%
“…The basic end-state comfort paradigm has been applied to assess motor planning in different age groups (e.g. Adalbjornsson et al 2008;Thibaut and Toussaint 2010), with clinical populations (e.g. Hughes 1996;Steenbergen et al 2000;van Swieten et al 2010), in monkeys (Chapman et al 2010;Weiss et al 2007), and also for different continuous tasks (Cohen and Rosenbaum 2004;Schütz et al in press;Zhang and Rosenbaum 2008).…”
Section: The End-state Comfort Effectmentioning
confidence: 99%
“…Two other studies showed that the end-state comfort eVect is manifested in nonhuman animals (Chapman, Weiss, & Rosenbaum, 2010;Weiss, Wark, & Rosenbaum, 2007). Several studies also showed a marked developmental trend for the end-state comfort eVect, with the eVect not taking hold until 9 years of age for typically developing children (Adalbjornsson, Fischman, & Rudisill, 2008;Thibaut & Toussaint, 2010;van Swieten et al, 2010), whereas the end-state comfort eVect is compromised in children with autism (Hughes, 1996), in children with developmental coordination disorder (van Swieten et al, 2010), and in adults with cerebral palsy (Steenbergen, Hulstijn, & Dortmans, 2000). For reviews, see Rosenbaum (2010) and Rosenbaum, Cohen, Meulenbroek, and Vaughan (2006).…”
Section: Introductionmentioning
confidence: 95%